Curriculum Development of Educational Units (KSP) at the Elementary/MI Level in the Implementation of the Independent Curriculum: Literature Study - Yulia Angga Anggraina; Sukiman Sukiman (Sekolah Tinggi Ilmu Al-Qur'an (SIQ) Amuntai Kalimantan Selatan, 2026)
This article aims to systematically examine the development of the Education Unit Curriculum (KSP) at the elementary/middle school level in the context of the implementation of the Independent Curriculum. This research uses a literature study method by examining various relevant national and international sources, especially reputable scientific publications in the last ten years. The results of the study show that the Curriculum of the Education Unit has a strategic role as an instrument that bridges national curriculum policies with contextual learning practices at the level of educational units. The effective development and implementation of the Education Unit Curriculum is influenced by several key factors, including the competence of teachers as learning designers, the leadership of school principals as learning leaders, collaborative culture in the school environment, and sustainable curriculum reflection and evaluation mechanisms. In addition, the Curriculum of the Education Unit provides a space of autonomy for schools to integrate student characteristics, local potential, and character and religious values into learning. However, this study also identified a number of challenges, such as the limitation of teacher capacity and the tendency of the Curriculum of the Education Unit to become an administrative document if it is not supported by systematic mentoring and evaluation. The findings of this literature study are expected to make a conceptual contribution to strengthening school-based curriculum development practices and become a reference for policy makers and basic education practitioners in optimizing the implementation of KSP in elementary and secondary schools.